1995
DOI: 10.1051/mmm:1995106
|View full text |Cite
|
Sign up to set email alerts
|

EELS-ESI Identification of Heterogeneous Suspensions of Aquatic Microparticles

Abstract: Abstract. 2014 Submicron mineral particles in freshwaters represent an important proportion of the total particle number. These microparticles are frequently associated to macromolecular organic matter and have a high specific surface area; they might thus be strong heavy metal and nutrient scavengers in aquatic systems. Their non-artefacted characterization at the level of individual particles represents a promising challenge, while preservation of the undisturbed state of natural fragile specimens is a prer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…On the contrary, EELS, which directly measures the energy loss of incident electrons inelastically scattered from atoms, is a direct probe of the electron configuration around atoms and can determine the oxidation state of 3d and 4d transition metals with a high spatial resolution [9][10][11]. TEM-EELS techniques have been used for many years in Materials Sciences and have recently found applications in biology and environmental sciences [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, EELS, which directly measures the energy loss of incident electrons inelastically scattered from atoms, is a direct probe of the electron configuration around atoms and can determine the oxidation state of 3d and 4d transition metals with a high spatial resolution [9][10][11]. TEM-EELS techniques have been used for many years in Materials Sciences and have recently found applications in biology and environmental sciences [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For the characterization of aquatic particles ( Mavrocordatos et al ., 1994 ; Perret et al ., 1995 ), we use mainly EELS on whole‐mount specimens analysed at 80 keV with an on‐column Castaing–Henry energy filter (EF‐TEM; Castaing & Henry, 1962). The variable thickness of the particles under investigation means that special attention should be given to the interpretation of the results because of spatial inhomogeneities in multiscattering processes originating from thick regions, and because of weak signals produced by thin regions of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [18,24] we have shown with aquatic suspensions (mineral particles and organic matter) that EF-TEM can be applied to (i) elemental analysis (spectrum mode; electron energy loss spectrometry, EELS-TEM), (ii) elemental mapping (imaging mode; electron spectroscopic Imaging, ESI-TEM), and (iii) the visualization of organic matter (structure-sensitive mode; contrast tuning, CT-TEM). The last technique has been selected and optimized in this work to enhance contrasting of polysaccharide fibrils.…”
Section: Analytical Electron Microscopymentioning
confidence: 99%